Arterial Blood Gas Analysis in Breath-Hold Divers at Depth - Bosco, Gerardo; Rizzato, Alex; Martani, Luca; Schiavo, Simone; Talamonti, Ennio; Garetto, Giacomo; Paganini, Matteo; Camporesi, Enrico M.; Moon, Richard E. (Frontiers in Physiology, 2018)
The present study aimed to evaluate the partial pressure of arterial blood gases on breath-hold divers performing a submersion at 40 m. Eight breath-hold divers were enrolled for the trials held at “Y-40 THE DEEP JOY” pool (Montegrotto Terme, Padova, Italy). Prior to submersion, an arterial cannula in the radial artery of the non-dominant limb was positioned. All divers performed a sled-assisted breath-hold dive to 40 meters. Three blood samplings occurred: at 10 minutes prior to submersion, at 40 meters depth, and within 2 minutes after diver’s surfacing and after resuming normal ventilation. Blood samples were analyzed immediately on site. Six subjects completed the experiment, without diving-related problems. The theoretically predicted hyperoxia at the bottom was observed in 4 divers out of 6, while the other 2 experienced a reduction in the partial pressure of oxygen (paO2) at the bottom. There were no significant increases in arterial partial pressure of carbon dioxide (paCO2) at the end of descent in 4 of 6 divers, while in 2 divers paCO2 decreased. Arterial mean pH and mean bicarbonate (HCO3-) levels exhibited minor changes. There was a statistically significant increase in mean arterial lactate level after the exercise. Ours was the first attempt to verify real changes in blood gases at a depth of 40 m during a breath-hold descent in free-divers. We demonstrated that, at depth, relative hypoxemia can occur, presumably caused by lung compression. Also, hypercapnia exists at depth, to a lesser degree than would be expected from calculations, presumably because of pre-dive hyperventilation and carbon dioxide distribution in blood and tissues.